Weeds Control in Cassava Plants Development - A. Nur Nasyfah Bongkang (Journal La Lifesci, 2021)
The purpose of this study is to determine what kinds of weeds may interfere with the development of cassava and how to manage the presence of weeds that interfere with the growth of cassava. Cassava has significant economic and social potential as a future food component, raw material for a variety of businesses, and animal feed, among other applications. Weeds have the ability to multiply quickly via seed. Annual weeds are the most common kind of weed discovered in cassava because they develop extremely quickly and generate seeds in a short period of time. Weed management is often accomplished by mechanical techniques, such as pulling, submerging, or other similar methods. Uprooting should be done before the seeds of this plant begin to spread, and additional methods of management should include herbicide spraying